IMPROVING THE QUALITY OF STUDENTS' CHARACTERS THROUGH THE APPLICATION OF HABITATION METHODS IN LEARNING PAI AT MTs GUPPI DANTE KOA, ENREKANG DISTRICT - Djollong, Andi Fitriani Djollong; Muis, Andi Abd.; Salmiati, Salmiati; Nurlailah, Nurlailah; Makki, Makki; Cemek, Nurasni (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research aims to describe improving the moral quality of students through the application of habituation methods in PAI learning at MTs Guppi Dante Koa, Enrekang Regency. The type of research used is descriptive qualitative. Data sources are primary data (Islamic religious education teachers, school principals and students) and secondary data in the form of articles and photo documentation. The research instrument uses observation guidelines, interview guidelines, and documentation guidelines. Data analysis techniques are data reduction, data presentation, and drawing conclusions. Research conclusions: 1) The moral description of students shows good morals during the learning process and daily activities by prioritizing polite, honest and disciplined learning and participating in all school activities starting from the learning process, congregational prayers, reciting the Koran and lectures to the assignments of the eye teacher Islamic religious education lessons. 2) The habituation method in learning Islamic religious education is carried out routinely and consistently starting from the training stage until it becomes a good habit in the learning process. 3) Implementation of the habituation method in PAI learning with students' morals shows effective results, manifested from students' enthusiasm and participation in congregational worship activities as well as showing good manners and learning discipline.